Twin Pregnancy Complicated By Interlocking: A Case Report - Kutlu, Tayfun; Bağlam, Elif; Eren, Sadiye (Gynecology Obstetrics & Reproductive Medicine, 2006)
Management of labor in multiple pregnancies is one of the most attracting subjects of obstetrics. Presentation of twin pairs is the major determinant of the route of deliv ery. In the past how to deliv er breech v ertex twin pairs was a conf licting decision. Anesthesia, technical difficulties and antibiotic options restricted the use of cesarean section. Under such circumstances ev en sacrif ication of one of the babies could be acceptable and thus mortality and morbidity was high. Recently we pref er the abdominal route f or delivery of breech vertex twins. Maternal morbidity is only slightly increased in cesarean sections when compared to vaginal deliv ery with the innovations of today. We now present a case of breech vertex twins which were interlocked during v aginal deliv ery and the f irst twin could be deliv ered up to the scapulas. The delivery of the first breech twin could be completed only after the abdominal deliv ery of the second v ertex twin. The babies both did very well in contrast to their difficult deliv ery. This condition presented a chance for us to rev iew the management of deliv ery of breech v ertex twin pairs in the literature and to present our own clinical experience.